Análise termodinâmica e de transferência de calor para dimensionamento de um sistema de refrigeração por absorção para aplicações em baixas temperaturas usando gás natural - Silva, Josinaldo Calixto da (2009)
The absorption refrigeration cycle studied in this work it uses as working fluid a mixture of water and ammonia and it is fed by thermal energy provided by direct burning of the natural gas. The objective is to produce cold in low temperatures for applications in the conservation of foods in general, especially in areas less favored by the electric net, as the fishing sector, or even for economical subjects of electric power rationing. The used cycle presents two sections of recovery interns of heat - one in the generator and the other in the absorber - for reduction in the amount of thermal energy supplied by burning natural gas directly. For a fixed temperature of cooling, the input parameters are optimized to obtain the best coefficient of performance based on the second law of thermodynamics. From the obtained results of the thermodynamics analysis, it is made the analysis of the transfer of heat for dimensionar the devices of the system where transfer of heat occurs. All simulation of the cycle was made with the creation of a code computacional in programming platform EES.